Virus-induced gene silencing - XU You-ping; XU Qiu-fang; SONG Xiao-yi; ZHANG Zhi-xin; CAI Xin-zhong (浙江大学学报. 农业与生命科学版)
The term virus-induced gene silencing' (VIGS) was first used to describe the phenomenon of recovery from virus infection, a natural plant antiviral mechanism, which recently has been exploited as a genetic technique involving recombinant viruses with a target gene fragment insert to knock down expression of endogenous target genes, and thereby analyse gene functions. VIGS is triggered by small interfering RNA (siRNA), whose single strand associates with RNA-induced silencing complex (RISC), which specifically binds to and thereafter degrades target RNA that is homologous to the siRNA. Fifteen VIGS vectors have been exploited from different types of viruses. The VIGS efficiency is significantly affected by the fragment inserted into the vector, the method for vector delivery, the host developmental stage when used for VIGS induction and the growth conditions of plants after VIGS induction treatment. As a novel technical tool for gene identification and functional analysis, VIGS has many advantages such as no necessity to know full-length sequences of the target genes, rapidness to obtain phenotype and avoiding construction of transgenic plants, and thus has been applying more and more broadly and extensively to plant gene functional analysis.